Synthesis of novel amidines via one-pot three component reactions: Selective topoisomerase I inhibitors with antiproliferative properties - El-Sheref, Essmat M.; Tawfeek, Hendawy N.; Hassan, Alaa A.; Bräse, S.; Elbastawesy, Mohammed A. I.; Gomaa, Hesham A. M.; Mostafa, Yaser A.; Youssif, Bahaa G. M. (Frontiers in Chemistry, 2022)
Novel series of amidines were synthesized via the interaction between alicyclic amines, cyclic ketones, and a highly electrophilic 4-azidoquinolin-2(1H)-ones without any catalyst or additive. All the obtained products were elucidated based on NMR spectroscopy, mass spectrometry, and elemental analysis. The reaction conditions were optimized using cyclohexanone (2), piperidine (3a), and 4-azido-quinolin-2(1H)-one (1a) under an air atmosphere. The new compounds 4a-l and 5a-c were tested for antiproliferative activity against four cancer cell lines using doxorubicin as a reference drug. The most potent derivatives were compounds 4b, 4d, 4e, 4i, and 5c, with GI50 ranging from 1.00 µM to 1.50 µM. Compound 5c was the most effective derivative against the four cancer cell lines, outperforming doxorubicin. The compounds 4b, 4d, 4e, 4i, and 5c were studied further as topoisomerase I and IIα inhibitors. The compounds tested showed selective inhibition of topo I over topo IIα. Finally, docking studies explain why these compounds prefer topo I over topo IIα.